Introduction - issue 78 - Mabro, R (Oxford Institute for Energy Studies, 2009)
Since the election of Barack Obama to the presidency of the United States, energy and climate change policies have moved from the back to the front stage of federal government political actions. Under the previous administration there was more rhetoric than effective legislative activity. The most remarkable statement was President Bush’s desire ‘to cure Americans addiction to oil’. But, how? This was never said in a realistic and effective way. To be sure, California and other states introduced innovative energy policies, but the writ of a state does not extend outside its border although its actions may encourage other states to introduce similar measures. The Obama initiatives are significant considering the increasing public concerns with climate change and the need for the USA to play a leading role in international negotiations on this critical issue; until recently it was seen as an obstacle rather than a force for good in the international climate change field. For these reasons we invited distinguished authors to present their views on the new US policies and initiatives.